Editor's Choice – Assessment of International Outcomes of Intact Abdominal Aortic Aneurysm Repair over 9 Years. (July 2017) - Budtz-Lilly, J.; Venermo, M.; Debus, S.; Behrendt, C.-A.; Altreuther, M.; Beiles, B.; Szeberin, Z.; Eldrup, N.; Danielsson, G.; Thomson, I.; Wigger, P.; Björck, M.; et al.
Abstract : Background: Case mix and outcomes of complex surgical procedures vary over time and between regions. This study analyses peri-operative mortality after intact abdominal aortic aneurysm (AAA) repair in 11 countries over 9 years. Methods: Data on primary AAA repair from vascular surgery registries in 11 countries for the years 2005–2009 and 2010–2013 were analysed. Multivariate adjusted logistic regression analyses were carried out to adjust for variations in case mix. Results: A total of 83, 253 patients were included. Over the two periods, the proportion of patients ≥80 years old increased (18.5% vs. 23.1%; p < .0001) as did the proportion of endovascular repair (EVAR) (44.3% vs. 60.6; p < .0001). In the latter period, 25.8% of AAAs were less than 5.5 cm. The mean annual volume of open repairs per centre decreased from 12.9 to 10.6 between the two periods ( p < .0001), and it increased for EVAR from 10.0 to 17.1 ( p < .0001). Overall, peri-operative mortality fell from 3.0% to 2.4% ( p < .0001). Mortality for EVAR decreased from 1.5% to 1.1% ( p < .0001), but the outcome worsened for open repair from 3.9% to 4.4% ( p = .008). The peri-operative risk was greater for octogenarians (overall, 3.6% vs. 2.1%, p < .0001; open, 9.5% vs. 3.6%, p < .0001; EVAR, 1.8% vs. 0.7%, p < .0001), and women (overall, 3.8% vs. 2.2%, p < .0001; open, 6.0% vs. 4.0%, p < .0001; EVAR, 1.9% vs. 0.9%, p < .0001). Peri-operative mortality after repair of AAAs <5.5 cm was 4.4% with open repair and 1.0% with EVAR, p < .0001. Conclusions: In this large international cohort, total peri-operative mortality continues to fall for the treatment of intact AAAs. The number of EVAR procedures now exceeds open procedures. Mortality after EVAR has decreased, but mortality for open operations has increased. The peri-operative mortality for small AAA treatment, particularly open surgical repair, is still considerable and should be weighed against the risk of rupture.